2011
DOI: 10.1587/nolta.2.263
|View full text |Cite
|
Sign up to set email alerts
|

The irrelevance of electric power system dynamics for the loading margin to voltage collapse and its sensitivities

Abstract: Abstract:The loading margin to a saddle-node or fold bifurcation measures the proximity to voltage collapse blackouts of electric power transmission systems. Sensitivities of the loading margin can be used to select controls to avoid voltage collapse. We analytically justify the use of static models to compute loading margins and their sensitivities and explain how the results apply to underlying dynamic models. The relation between fold bifurcations of the static models and saddle-node bifurcations of the und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 43 publications
1
22
0
7
Order By: Relevance
“…Therefore, injecting more reactive powers into the network may shorten the robust stability region relatively. 3) Effect of exciter gain K: The model of exciter is described in (25). In this section, effect of exciter gain K is analyzed in Table IV.…”
Section: A Robust Stable Point Smentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, injecting more reactive powers into the network may shorten the robust stability region relatively. 3) Effect of exciter gain K: The model of exciter is described in (25). In this section, effect of exciter gain K is analyzed in Table IV.…”
Section: A Robust Stable Point Smentioning
confidence: 99%
“…It has been noted in [25] that traditional "voltage collapse" instability is not affected by the load dynamics as it corresponds to saddle-node bifurcation, where the equilibrium point disappears altogether. At the same time for the more common Hopf bifurcation it was argued in [26] that sensitivity analysis of the system trajectories may provide enough information to assess the risks associated with common disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…However, analyses based on static approaches present some practical advantages over the dynamical approaches [2]. Analyses based on static approaches have been widely used, since they provide results with acceptable accuracy and little computational effort.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies showed that the small-disturbance stability analysis of power system voltage stability can be based on the power flow (PF) equation [5][6][7][8]. Among them, saddle-node bifurcation (SNB) and limit-induced bifurcation (LIB) associated with the PF equation are two kinds of mechanisms that lead to voltage collapse [3,4,9,10].…”
Section: Introductionmentioning
confidence: 99%